ANALISIS MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP PEMAHAMAN DAN PENALARAN LOGIS MAHASISWA - Tambunan, Janwar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2021)
This study aims to determine whether the increase in students' understanding ability with the blended learning learning model is better than the understanding ability of students whose learning uses conventional learning models in terms of every aspect of understanding ability and whether the increase in students' logical reasoning with the blended learning learning model is better than students' logical reasoning. with conventional learning models. This study uses a quantitative research approach with experimental methods in the form of quasi-experiments. The population in this study were students of the Christian religious education study program, FKIP University HKBP Nommensen. The population was taken randomly (Cluster Random Sampling). The instrument used consisted of a test of understanding and logical reasoning in the form of a description. The instrument was declared to have met the requirements of content validity and reliability coefficient. Based on the results of the analysis, the research results obtained that the increase in students' understanding abilities with the blended learning learning model is better than the understanding abilities of students whose learning uses conventional learning models, and the increase in students' logical reasoning with the blended learning learning model is better than the logical reasoning of students with conventional learning models